2001
DOI: 10.1212/wnl.57.6.1112
|View full text |Cite
|
Sign up to set email alerts
|

A pilot tolerability and efficacy study of levetiracetam in patients with chronic myoclonus

Abstract: Levetiracetam was recently approved as adjunctive therapy for partial onset seizures. The authors conducted an open-label trial of levetiracetam in eight patients with chronic myoclonus. Patients were assessed by using the Unified Myoclonus Rating Scale. Levetiracetam was well tolerated. Three of five patients with cortical myoclonus experienced reductions in their myoclonus scores, providing support for a larger, placebo-controlled trial in cortical myoclonus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 8 publications
1
52
1
1
Order By: Relevance
“…Myoclonus in DLB and PD consists of a sudden brief jerk that is accompanied by a sharp transient in the contralateral sensorimotor cortex on EEG 39, 43. This type of myoclonus, called cortical myoclonus, may be caused by aberrant cortical excitability39, 43, 44 and has been successfully treated with anti‐epileptic drugs 52, 53, 54. In our study, myoclonus was associated with an earlier age of onset of cognitive impairment, raising the possibility that aberrant network excitability may contribute to cognitive dysfunction in DLB.…”
Section: Discussionmentioning
confidence: 99%
“…Myoclonus in DLB and PD consists of a sudden brief jerk that is accompanied by a sharp transient in the contralateral sensorimotor cortex on EEG 39, 43. This type of myoclonus, called cortical myoclonus, may be caused by aberrant cortical excitability39, 43, 44 and has been successfully treated with anti‐epileptic drugs 52, 53, 54. In our study, myoclonus was associated with an earlier age of onset of cognitive impairment, raising the possibility that aberrant network excitability may contribute to cognitive dysfunction in DLB.…”
Section: Discussionmentioning
confidence: 99%
“…Frucht and Fahn (2000) reviewed more than 100 cases of LAS and found that clonazepam, sodium valproate, and piracetam were significantly effective in approximately 50% of patients. Recently, several groups have confirmed the efficacy of levetiracetam in PHM (Frucht et al, 2001;Krauss et al, 2001;Lim and Ahmed, 2005). Clonazepam, sodium valproate, piracetam, and levetiracetam may be recommended as first-line agents to treat patients with LAS.…”
Section: Discussionmentioning
confidence: 99%
“…18 Case reports and small open-label trials indicate that LEV reduces cortical reflex myoclonus due to various causes and is generally well tolerated. 37 Another case report found that piracetam reduced choreoathetosis. 38 Loscher and Richter studied the effects of LEV and piracetam in a mutant hamster model of paroxysmal dystonia, a form of idiopathic generalized dystonia, and found that both drugs significantly decreased the severity of dystonia.…”
Section: Discussionmentioning
confidence: 99%